PEMANFAATAN API INDODAX PADA PERDAGANGAN ASET DIGITAL CRYPTO BERBASIS WEBSITE - Novera Kristianti; Viktor Handrianus Pranatawijaya (Jurnal Teknologi Informasi: Jurnal Keilmuan dan Aplikasi Bidang Teknik Informatika, 2023)
The development of information technology today originated from advances in the field of computerization by giving birth to many new technologies such as block chain technology. One of the products born of block chain technology is cryptocurrency. Cryptocurrency is a digital currency that has the main characteristic of being transparent because it is a public ledger, all transactions are recorded online so that anyone can see where and where the coins are flowing from and where. To assist in the process of trading, an application is needed that can automatically carry out trading activities. The application that was built as a solution to this is a crypto marketplace website using the waterfall method in system design, starting from analyzing software needs, design, implementation, and testing. The results show that this system has successfully implemented the Indodax API which is used to see prices and other information about the bitcoin market and can buy and sell bitcoin ups and downs in crypto prices in the market, and can see information in the form of market activities, BTC / IDR market charts, and can even see transaction history.